Thymoquinone Poly(lactide-co-glycolide) Nanoparticles Exhibit Enhanced Anti-proliferative, Anti-inflammatory, and Chemosensitization Potential - Ravindran, Jayaraj (2010)
Thymoquinone (TQ), derived from the medicinal spice Nigella sativa (also called black cumin), has been shown to exhibit anti-inflammatory and anti-cancer activities. In this report we employed polymer-based nanoparticle approach to improve upon its effectiveness and bioavailability. TQ was encapsulated with 97.5% efficiency in biodegradable nanoparticulate formulation based on poly (lactide-co-glycolide) (PLGA) and the stabilizer polyethylene glycol (PEG)-5000. Dynamic laser light scattering and transmission electron microscopy confirmed particle diameter ranged between 150–200 nm. Electrophoretic gel shift mobility assay showed that TQ nanoparticles (NP) were more active than TQ in inhibiting NF-κB activation and in suppressing the expression of cyclin D1, matrix metalloproteinase (MMP)-9, vascular endothelial growth factor (VEGF), markers of cell proliferation, metastasis and angiogenesis, respectively. TQ-NP was also more potent than TQ in suppressing proliferation of colon cancer, breast cancer, prostate cancer, and multiple myeloma cells. Esterase staining for plasma membrane integrity revealed that TQ-NP was more potent than TQ in sensitizing leukemic cells to TNF- and paclitaxel-induced apoptosis. Overall our results demonstrate that encapsulation of TQ into nanoparticles enhances its anti-proliferative, anti-inflammatory, and chemosensitizing effects.